HCV novel therapeutic regimens in Wonderland: A budget impact analysis in the Lombardy Region. Issue 10 (October 2016) - Garagiola, Elisabetta; Ferrario, Lucrezia; Croce, Davide; Menzaghi, Barbara; Quirino, Tiziana; Rizzardini, Giuliano; Foglia, Emanuela
Abstract: Background: The advent of new HCV drugs has generated widespread economic concerns, particularly within the Italian setting, characterized by continuous linear cuts and spending review actions. The overall trade-off between investments and savings needs an in depth analysis. Aims: The study aimed to estimate the budget impact of the introduction of the novel drugs approved during the year 2015, compared with the historical situation based on the different treatment options available prior to 2015. Methods: A three-year budget impact model was developed, taking into consideration the Lombardy Region (Northern Italy) Health Service perspective. The degree of liver fibrosis, genotypes, presence of only HCV or HIV/HCV co-infections, presence or absence of sustained virological response, and direct healthcare total costs were the variables of the model. Results: With the introduction of the novel regimens, a higher number of HCV patients achieved a sustained virological response (+20%). Further analysis showed that an investment in innovative technologies would have given the Regional System significant economic savings within the 36-month period (−6.64%/−7.15%). Conclusions: Treating HCV-infected persons in the Lombardy Region with the new drugs would reduce healthcare expenditure on this specific disease, in each forecast implemented, thus reducing the economic burden of the pathology.